AN ANALYSIS OF FIGURATIVE LANGUAGE IN SONG LYRICS OF THE ALBUM “MIDNIGHTS” BY TAYLOR SWIFT - Pelsi Santika; Syafryadin Syafryadin (Universitas Wiralodra, 2023)
This study aims to discover the figurative language and its meaning in the song lyrics used in the